Perancangan Sistem Informasi Deteksi dan Pemantauan Stunting Balita di Desa Melalui SIHARAPAN - Alal Lestari; Ridha Rahma Tina; Ferdiyansyah Achmad; Fathurrahmani; Agustian Noor (LPPM Universitas Potensi Utama, 2024)
The nutritional health of children is a crucial matter to consider, given its significant impact on physical and cognitive development. Therefore, early nutritional detection in infants and toddlers is highly necessary to identify whether the obtained nutrition is sufficient. This is done to prevent children from experiencing stunting conditions, which can affect educational quality, morbidity, and productivity in adulthood. In addressing these issues and challenges related to limited health resources and manual data recording systems, the development of the SIHARAPAN application (Information System to Prevent Low Intake of Food and Nutrition in Children) becomes a highly important solution. This application aims to facilitate the management of infant and toddler nutritional health data in integrated health posts (posyandu), as well as a tool to identify symptoms of stunting in children. The application is designed to streamline administration and management of nutritional status data in children through a technological approach. This research applies a waterfall approach in development, starting from system requirements analysis, system design, coding using the CodeIgniter 4 framework based on the PHP programming language, and implementing z-score formulas to determine nutritional status in children, as well as testing using black box testing. The test results indicate that the SIHARAPAN application runs 100% successfully according to its functions, improving information accessibility for posyandu cadres and related parties to prevent stunting and facilitate coordination in child health care.